Perlindungan Hukum Bagi Korban Salah Tangkap yang Mengalami Kekerasan dalam Proses Penyidikan - Ilham Ilham; Asbullah Thamrin; Danil Danil; Nurmiati Muhiddin (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
The goals of this study are to 1) investigate the types of punishments that can be handed out to law enforcement officers who are found to have participated in wrongful arrests that were accompanied by acts of violence, and 2) investigate the types of responsibilities that the state has toward victims of wrongful arrests who were subjected to acts of violence during the investigation process. This study makes use of legal materials in the form of statutory regulations, in addition to legal materials obtained through literature or literature studies, such as books in the field of legal science, research results, draft laws and regulations, research results, the internet, and other sources that are closely related to one another about the issue that is being investigated. Following the collection of all legal materials, these are then categorized and analyzed to draw conclusions based on the information obtained from the issues that were discussed. The findings demonstrate that the occurrence of wrongful arrests is evidence of a fundamental management distortion that ignores the importance of professionalism in the collection of evidence. In this particular instance, the ethics code that governs the police profession has been broken. The members of the police force who were involved in the incident are also subjected to disciplinary action. This occurs by the Police Code of Ethics as well as Regulation Number 2 of 2003 issued by the Head of the National Police of the Republic of Indonesia concerning the Order of Police Members. While this is going on, the victim has the legal right to file a lawsuit, specifically requesting a pretrial order that the defendant pays compensation and provides rehabilitation following the KUHAP.